2018
DOI: 10.1002/jsde.12017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophobic Modification on the Properties of Polymer‐Blended Microemulsion Gels

Abstract: Phase behavior of sodium oleate (NaOl)/isoamyl alcohol‐based lamellar gel phase in cedar oil/water medium in the presence of the nonionic polymer hydroxyethyl cellulose (HEC) and its hydrophobic modified product (HMHEC) is investigated for the development of polymer‐embedded surfactant gels. HMHEC is more soluble in oil‐in‐water (o/w) microemulsions, but nonionic HEC shows limited solubility in the lamellar microemulsion (o/w type). Quantitative estimation of rate of adsorption of the polymer on lamellae bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Compared with traditional polymer gels, interpenetrating polymer network gels have a special network structure, and due to synergistic effect between polymer molecular chains, they possess shear resistance, plugging ability, profile improvement ability and wash‐resistance. Therefore, the interpenetrating polymer network gel shows great application potential in profile control plugging . Jia H et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional polymer gels, interpenetrating polymer network gels have a special network structure, and due to synergistic effect between polymer molecular chains, they possess shear resistance, plugging ability, profile improvement ability and wash‐resistance. Therefore, the interpenetrating polymer network gel shows great application potential in profile control plugging . Jia H et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interpenetrating polymer network gel shows great application potential in profile control plugging. [23][24][25] Jia H et al demonstrated that resorcinol/phenolformaldehyde/HPAM secondary cross-linking gel system can be used for water shutoff in fractured reservoirs. In addition, the strength of the secondary cross-linked gel system can be changed/varied by adjusting the concentration of components to satisfy well site requirements.…”
Section: Introductionmentioning
confidence: 99%